HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP TINDAKAN WANITA PEKERJA SEKSUAL TIDAK LANGSUNG DI HOTSPOT X KECAMATAN TENAYAN RAYA PEKANBARU TENTANG PAP SMEAR DAN INSPEKSI VISUAL ASETAT SEBAGAI DETEKSI DINI KANKER SERVIKS - Hermanto "; Wiwit Ade Fidiawati; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTCervical cancer is a malignant disease in the epithelial cells of the cervix which still ranks as the fourth most common cancer in women worldwide. Indirect Female Sex Workers (FSW) have a higher risk of cervical cancer. This study aims to determine the correlation between knowledge and attitudes toward the behavior of indirect FSW at hotspot X District Tenayan Raya Pekanbaru about Pap smears and Visual Inspection with Acetic Acid (VIA) as an early detection of cervical cancer. The method of this research is analytic cross sectional. The study population is indirect FSW residing in the hotspot X District Tenayan Raya Pekanbaru and samples were taken with total sampling method to 66 people through interviews using questionnaire. The results showed that among 66 respondents, 44 respondents (66.7%) have bad knowledge, 16 respondents (24.2%) have moderate knowledge and 6 respondents (9.1%) have good knowledge. In the questionnaire, 39 respondents (59.1%) have a negative attitude and 27 respondents (40.9%) have a positive attitude. In the examination, 44 respondents (66.7%) did Pap Smear and VIA test and 22 respondents (33.3%) did not do Pap Smear and VIA test. There is a correlation between knowledge and attitude (p = 0.022) and correlation between attitude and action (p = 0.034) but there is no correlation between knowledge and action (p = 0.948). It is concluded that the majority of Indirect FSW at hotspot X District Tenayan Raya Pekanbaru has poor knowledge, negative attitudes but has good action on early detection of cervical cancer.Keywords: knowledge, attitude, behaviour, indirect female sex workers, pap smears, VIA, Hotspot X